Essential Role of Enterovirus 2A Protease in Counteracting Stress Granule Formation and the Induction of Type I Interferon - Visser, Linda J; Langereis, Martijn A; Rabouw, Huib H; Wahedi, Maryam; Muntjewerff, Elke M; de Groot, Raoul J; van Kuppeveld, Frank J M (Journal of virology, 2019)
Most viruses have acquired mechanisms to suppress antiviral alpha/beta interferon (IFN-α/β) and stress responses. Enteroviruses (EVs) actively counteract the induction of IFN-α/β gene transcription and stress granule (SG) formation, which are increasingly implicated as a platform for antiviral signaling, but the underlying mechanisms remain poorly understood. Both viral proteases (2A and 3C ) have been implicated in the suppression of these responses, but these conclusions predominantly rely on ectopic overexpression of viral proteases or addition of purified viral proteases to cell lysates. Here, we present a detailed and comprehensive comparison of the effect of individual enterovirus proteases on the formation of SGs and the induction of IFN-α/β gene expression in infected cells for representative members of the enterovirus species EV-A to EV-D. First, we show that SG formation and IFN-β induction are suppressed in cells infected with EV-A71, coxsackie B3 virus (CV-B3), CV-A21, and EV-D68. By introducing genes encoding CV-B3 proteases in a recombinant encephalomyocarditis virus (EMCV) that was designed to efficiently activate antiviral responses, we show that CV-B3 2A , but not 3C , is the major antagonist that counters SG formation and IFN-β gene transcription and that 2A 's proteolytic activity is essential for both functions. 2A efficiently suppressed SG formation despite protein kinase R (PKR) activation and α subunit of eukaryotic translation initiation factor 2 phosphorylation, suggesting that 2A antagonizes SG assembly or promotes its disassembly. Finally, we show that the ability to suppress SG formation and IFN-β gene transcription is conserved in the 2A of EV-A71, CV-A21, and EV-D68. Collectively, our results indicate that enterovirus 2A plays a key role in inhibiting innate antiviral cellular responses. Enteroviruses are important pathogens that can cause a variety of diseases in humans, including aseptic meningitis, myocarditis, hand-foot-and-mouth disease, conjunctivitis, and acute flaccid paralysis. Like many other viruses, enteroviruses must counteract antiviral cellular responses to establish an infection. It has been suggested that enterovirus proteases cleave cellular factors to perturb antiviral pathways, but the exact contribution of viral proteases 2A and 3C remains elusive. Here, we show that 2A , but not 3C , of all four human EV species (EV-A to EV-D) inhibits SG formation and IFN-β gene transcription. Our observations suggest that enterovirus 2A has a conserved function in counteracting antiviral host responses and thereby is the main enterovirus "security protein." Understanding the molecular mechanisms of enterovirus immune evasion strategies may help to develop countermeasures to control infections with these viruses.